Research progress in mechanism of anticancer action of shikonin targeting reactive oxygen species - Qi, Ke; Li, Jiayi; Hu, Yang; Qiao, Yiyun; Mu, Yongping (Frontiers in Pharmacology, 2024)
Excessive buildup of highly reactive molecules can occur due to the generation and dysregulation of reactive oxygen species (ROS) and their associated signaling pathways. ROS have a dual function in cancer development, either leading to DNA mutations that promote the growth and dissemination of cancer cells, or triggering the death of cancer cells. Cancer cells strategically balance their fate by modulating ROS levels, activating pro-cancer signaling pathways, and suppressing antioxidant defenses. Consequently, targeting ROS has emerged as a promising strategy in cancer therapy. Shikonin and its derivatives, along with related drug carriers, can impact several signaling pathways by targeting components involved with oxidative stress to induce processes such as apoptosis, necroptosis, cell cycle arrest, autophagy, as well as modulation of ferroptosis. Moreover, they can increase the responsiveness of drug-resistant cells to chemotherapy drugs, based on the specific characteristics of ROS, as well as the kind and stage of cancer. This research explores the pro-cancer and anti-cancer impacts of ROS, summarize the mechanisms and research achievements of shikonin-targeted ROS in anti-cancer effects and provide suggestions for designing further antitumor experiments and undertaking further experimental and practical research.